1999
DOI: 10.1046/j.1442-2050.1999.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bombesin on esophageal motility in humans

Abstract: We have investigated the effect of bombesin on esophageal motility and explored the mechanism of action of bombesin. Eight healthy subjects were studied in random order during intravenous administration of (1) bombesin, (2) bombesin + vagal cholinergic receptor blockade with atropine and (3) bombesin + somatostatin. Lower esophageal sphincter pressure (LESP) and esophageal body motility were recorded continuously by Dent-sleeve manometry. Bombesin significantly (p < 0.01) increased LESP from 20 +/- 2 mmHg to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Although previous studies found that bombesin can increase LES contraction in opossums and LES pressure in humans, the bombesin receptor subtypes involved and the underlying mechanism are still not clear 13 14 . Here, we used porcine LES to investigate which of the bombesin receptor subtypes, BB 1 , BB 2 , and BB 3 , are involved in bombesin-induced LES contraction.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Although previous studies found that bombesin can increase LES contraction in opossums and LES pressure in humans, the bombesin receptor subtypes involved and the underlying mechanism are still not clear 13 14 . Here, we used porcine LES to investigate which of the bombesin receptor subtypes, BB 1 , BB 2 , and BB 3 , are involved in bombesin-induced LES contraction.…”
mentioning
confidence: 97%
“…Bombesin increases the LES pressure in humans and can affect esophageal motility by increasing peristaltic wave amplitude and duration. Neither the effects of vagal cholinergic agents nor the release of gastrointestinal hormones caused by bombesin are considered to be related to the mechanism of action of bombesin on esophageal motility in humans 14 .…”
mentioning
confidence: 99%